Feasibility of a single contrast bolus high-pitch pulmonary CT angiography protocol followed by low-dose retrospectively ECG-gated cardiac CT in patients with suspected pulmonary embolism = Evaluation eines high pitch CT Pulmonalisangiografieprotokolls mitunmittelbar folgender niedrigdosis retrospektiv getriggerter HerzCT Spirale unter Verwendung eines einzigen Kontrastmittelbolus beiPatienten mit Verdacht auf Lungenarterienembolie - Schäfer, Julia Carmen; Haubenreisser, Holger; Meyer, Mathias; Grüttner, Joachim; Walter, Thomas; Borggrefe, Martin; Schönberg, Stefan; Henzler, Thomas (RöFo, 2018)
Introduction: To prospectively evaluate the feasibility of single contrast bolus high-pitch CT pulmonary angiography (CTPA) subsequently followed by low-dose retrospectively ECG-gated cardiac CT (4D-cCT) in patients with suspected pulmonary embolism (PE) to accurately evaluate right ventricular (RV) function. Materials and Methods: 62 patients (33 female, age 65.1 ± 17.5 years) underwent high-pitch CTPA examination with 80cc of iodinated contrast material. 5 s after the end of the high-pitch CTPA study, a low-dose retrospectively ECG-gated cardiac CT examination was automatically started. The volume CT dose index (CTDI vol) and dose length product (DLP) were recorded in all patients and the effective dose was calculated. For the assessment of image quality, attenuation was measured as Hounsfield units (HUs) within various regions of interest (ROIs). These ROIs were used to calculate the signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR). Subjective image quality was assessed using a five-point Likert scale. On 4D-cCT, the ejection fraction of both ventricles (RVEF, LVEF) as well as the ratio of RVEF and LVEF (RVEF/LVEF) was assessed. The statistical difference of all parameters between the PE and non-PE group was calculated. Results: The mean effective radiation dose was 4.22 ± 2.05 mSv. Attenuation measurements on CTPA showed the highest attenuation values in the main pulmonary artery (442.01 ± 187.64). On 4D-cCT attenuation values were highest in the descending aorta (560.59 ± 208.81). The CNR and SNR values on CTPA were highest within the main pulmonary artery (CNR = 12.43 ± 4.57; SNR = 15.14 ± 4.90). On 4D-cCT images, the highest SNR and CNR could be measured in the descending aorta (CNR = 10.26 ± 5.57; SNR = 10.86 ± 5.17). The mean LVEF was 60.73 %± 14.65 %, and the mean RVEF was 44.90 %± 9.54 %. The mean RVEF/LVEF was 0.79 ± 0.29. There was no significant difference between the PE and non-PE group for either of the parameters. Conclusion: The investigated combined CTPA and 4D-cCT protocol is feasible using a single contrast bolus and allows the evaluation of RV function in patients with suspected PE. Further studies have to evaluate the additional value of this protocol regarding risk stratification in patients with PE. Key